Coco regulates dorsoventral specification of germ layers via inhibition of TGFβ signalling - Bates, Thomas J. D. (Company of Biologists, 2013)
One of the earliest steps in embryonic development is the specification of the germ layers, the subdivision of the blastula embryo into endoderm, mesoderm and ectoderm. Maternally expressed members of the Transforming Growth Factor β (TGFβ) family influence all three germ layers; the ligands are required to induce endoderm and mesoderm, whereas inhibitors are required for formation of the ectoderm. Here, we demonstrate a vital role for maternal Coco, a secreted antagonist of TGFβ signalling, in this process. We show that Coco is required to prevent Activin and Nodal signals in the dorsal marginal side of the embryo from invading the prospective ectoderm, thereby restricting endoderm- and mesoderm-inducing signals to the vegetal and marginal zones of the pre-gastrula Xenopus laevis embryo.